2014
DOI: 10.1177/1753193414541222
|View full text |Cite
|
Sign up to set email alerts
|

CT angiography-guided single-stage release of adjacent webspaces in non-Apert syndactyly

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Congenital syndactyly is the second most common congenital hand anomaly, which results from the failure of developmental separation of adjacent digital rays, and has an incidence of 1:2000 live births. [ 1 ] Congenital syndactyly has a strong familial tendency, and is usually bilateral. [ 2 , 3 ] The condition may present as an isolated abnormality, or in association with complex conditions such as Poland syndrome, Apert syndrome, or cleft hand.…”
Section: Introductionmentioning
confidence: 99%
“…Congenital syndactyly is the second most common congenital hand anomaly, which results from the failure of developmental separation of adjacent digital rays, and has an incidence of 1:2000 live births. [ 1 ] Congenital syndactyly has a strong familial tendency, and is usually bilateral. [ 2 , 3 ] The condition may present as an isolated abnormality, or in association with complex conditions such as Poland syndrome, Apert syndrome, or cleft hand.…”
Section: Introductionmentioning
confidence: 99%
“…The surgical protocol for CSM usually includes three key parts: separation of syndactyly, plasty of syndactylous webs, and surface coverage of the wound ( 4 , 15 , 26 , 27 ). Different surgical modes are chosen according to the bifurcation site of the hand vessels when the fingerwebs are separated and take shape ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Before surgery, it is crucial for surgeons to determine the bifurcation of the common palmar digital arteries (CPDAs) and the maturity of the proper palmar digital arteries (PPDAs) of the affected hand, which guarantees a better prognosis and prevention of serious vascular compromise ( 12 14 ). Currently, the imaging methods for preoperative assessment of palmar digital vessels include ultrasound, computed tomography angiography (CTA) and magnetic resonance imaging (MRI) ( 1 , 10 , 15 , 16 ). However, CTA involves ionizing radiation, and visualization of the soft tissue of hands is not satisfactory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preoperative evaluation of the soft and bony tissue elements in the syndactylized hand is necessary in every patient and done using conventional radiology images and computed tomography (CT) scan images. 3 Hynes et al 3 found that CT angiographically guided release of adjacent webspaces benefits the patient. However, CT imaging has numerous disadvantages, like radiation, costs, and need for anesthesia when used for children.…”
Section: Introductionmentioning
confidence: 99%